2008
DOI: 10.1261/rna.1293008
|View full text |Cite
|
Sign up to set email alerts
|

The role of the putative 3′ end processing endonuclease Ysh1p in mRNA and snoRNA synthesis

Abstract: Pre-mRNA 39 end formation is tightly linked to upstream and downstream events of eukaryotic mRNA synthesis. The two-step reaction involves endonucleolytic cleavage of the primary transcript followed by poly(A) addition to the upstream cleavage product. To further characterize the putative 39 end processing endonuclease Ysh1p/Brr5p, we isolated and analyzed a number of new temperature-and cold-sensitive mutant alleles. We show that Ysh1p plays a crucial role in 39 end formation and in RNA polymerase II (RNAP II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 70 publications
4
19
0
Order By: Relevance
“…The only change that we detect upon treatment with 4NQO is a decrease in subunits of CPF, the factor that recognizes the U-rich elements flanking the poly(A) site and provides the enzymatic functions of cleavage and poly(A) addition (Millevoi and Vagner 2010;Chan et al 2011). Mutations in CPF subunits cause a shift to downstream sites on common test genes such as RNA14 and ACT1 (Dichtl et al 2002;He et al 2003;Kyburz et al 2003;Garas et al 2008), similar to the changes seen for these transcripts upon exposure to 4NQO. We propose that the poorer configuration of processing signals found on suppressed promoter-proximal sites make them more susceptible to the reduced levels of CPF caused by 4NQO and thus more likely to be bypassed.…”
Section: Altering 39-end Processing At Poly(a) Sitessupporting
confidence: 51%
“…The only change that we detect upon treatment with 4NQO is a decrease in subunits of CPF, the factor that recognizes the U-rich elements flanking the poly(A) site and provides the enzymatic functions of cleavage and poly(A) addition (Millevoi and Vagner 2010;Chan et al 2011). Mutations in CPF subunits cause a shift to downstream sites on common test genes such as RNA14 and ACT1 (Dichtl et al 2002;He et al 2003;Kyburz et al 2003;Garas et al 2008), similar to the changes seen for these transcripts upon exposure to 4NQO. We propose that the poorer configuration of processing signals found on suppressed promoter-proximal sites make them more susceptible to the reduced levels of CPF caused by 4NQO and thus more likely to be bypassed.…”
Section: Altering 39-end Processing At Poly(a) Sitessupporting
confidence: 51%
“…A cleavage-dependent PAS-like mechanism was previously suggested for ncRNA termination (Fatica et al 2000;Morlando et al 2002;Garas et al 2008;Grzechnik and Kufel 2008;Kim et al 2010;Al Husini et al 2013). However, SNR13 and SNR33 were shown to require only the Pcf11 CID (Kim et al 2006).…”
Section: Pcf11 Mediates Nrd-dependent Termination Discussionmentioning
confidence: 95%
“…This provides a signal for binding many factors involved in 39-end formation, which in turn renders RNAPII competent for termination (Whitelaw and Proudfoot 1986;Logan et al 1987;Connelly and Manley 1988;Birse et al 1997;. In yeast, mutations and conditional depletion of factors involved in pre-mRNA cleavage and polyadenylation, including homologs of CstF-64 (Rna15), CstF-77 (Rna14), Pcf11, CPSF160 (Yhh1), CPSF-73 (Ysh1), and Ssu72, result in read-through at the 39-end of protein-coding genes (Birse et al 1998;Dichtl et al 2002;Steinmetz and Brow 2003;Garas et al 2008). Accordingly, ChIP assays suggest that 39-end processing factors, including Pcf11, Rna14, and Rna15, become associated with the RNAPII EC at the poly(A) site, in a Ser2 phosphorylated CTD-dependant manner (Ahn et al 2004;Kim et al 2004a;Luo et al 2006).…”
Section: Trans-acting Factor Dynamics At the Poly(a) Site Affect Tranmentioning
confidence: 99%
“…Kim et al (2006) also showed that cleavage by the cleavage/polyadenylation machinery is not required for snoRNA termination, as depletion of the CPSF-73 homolog Ysh1 or a mutation of PCF11 blocking cleavage did not affect snoRNA termination. However, transcription read-through was seen in strains expressing PCF11 mutants that are not capable of binding the CTD, and Garas et al (2008) showed that termination at specific snoRNA genes is defective in a particular cold-sensitive YSH1 mutant strain. Interestingly, as shown in mRNA termination, Steinmetz et al (2006a) observed that alteration of the heterodimer Rpb3/11 impairs snoRNAs termination.…”
Section: Involvement Of Mrna 39-end Processing Factors In Yeast Snornmentioning
confidence: 99%